Aumento del espacio entre caracteres: ¿mejora la lectura de alumnos con dificultades? - Ripoll Salceda, Juan C. (2015)
Some recent research suggests the possibility of improving the reading of students with dyslexia through a simple manipulation to increase the space between characters in the texts. We studied the effects of this change in the number of errors and correct words per minute in the reading of 14 students from first through third grade (elementary school) with reading difficulties. Students read two versions of the same text, one written with normal space between characters and another with increased space. Reading evaluations were blind. No significant differences were found in the number of reading errors or in the number of correct words per minute in the reading of these students, so caution and further research including a control of the difficulty of the texts are recommended before developing and implementing interventions for students with dyslexia based on space between characters.